2022
DOI: 10.2147/opth.s317017
|View full text |Cite
|
Sign up to set email alerts
|

Role of Socioeconomic Status (SES) in Globe Injuries: A Review

Abstract: Globe injury is a serious worldwide public health issue frequently leading to permanent vision impairment. The plethora of different types of globe injuries is classified into categories, including open and closed globe injuries. Globe injury occurs mainly in the workplace and at home, affecting predominantly middle-aged working men. Socioeconomic status (SES) is defined by income level, educational attainment, and employment status. Low socioeconomic status has been associated with a higher incidence of globe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Overall, greater neighborhood-level SVI is associated with a greater likelihood of non-adherence to ophthalmology appointments, and the largest difference in adherence was observed with the socioeconomic status SVI theme. Low socioeconomic status is associated with a higher incidence of open globe injury, 25 presenting at a more advanced stage of age-related macular degeneration, 26 a greater risk of developing glaucoma, 27 and higher rates of blindness. 28 Residency in more disadvantaged neighborhoods is associated with poor adherence to both diabetic retinopathy screening 29, 30 and physician recommended urgent ophthalmology appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, greater neighborhood-level SVI is associated with a greater likelihood of non-adherence to ophthalmology appointments, and the largest difference in adherence was observed with the socioeconomic status SVI theme. Low socioeconomic status is associated with a higher incidence of open globe injury, 25 presenting at a more advanced stage of age-related macular degeneration, 26 a greater risk of developing glaucoma, 27 and higher rates of blindness. 28 Residency in more disadvantaged neighborhoods is associated with poor adherence to both diabetic retinopathy screening 29, 30 and physician recommended urgent ophthalmology appointments.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 According to the American Academy of Ophthalmologists (AAO), three of the main risk factors for OFBs consist of metal-on-metal tasks, male gender, and lack of ocular protection. 6 It has been also postulated that the alteration in many factors, such as decrease in manual labour, rise of awareness, and improvements at the offered health services and safety, have led to a decrease in the incidence of OFBs in the developed countries. 23 In our study, 10.5% of the almost 5200 registered cases of our department in a three-month period had a foreign body in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that 55 million ocular injuries occur every year worldwide resulting in 16 million cases of bilateral blindness and 19 million cases of unilateral blindness. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there is an impact on socioeconomic status on the medical conditions that people experience (Chan et al, 2018). For example, a study confirmed that patients with lower SES were more likely to suffer from ocular trauma (Kousiouris et al, 2022).…”
Section: Family Capitalmentioning
confidence: 99%